Oxford handbook of legal correspondence - Haigh, Rupert (Oxford University Press, 2006)
Provides the information for writing legal correspondence, including emails, letters, faxes, memos, file notes, and CVs. This work includes: case studies modelled on real correspondence, and topics covering common and internationally relevant areas of legal practice. It is suitable for use in class, the office, or at home.